Electrochemical Study of Pencillin Benzyl Salt With Pb(II) in Non-Aqueous Media - SHARMA, SUNITA; GUPTA, O.D. (Asian Journal of Chemistry, 2010)
Using DME electrode the comparative investigation on the electroreduction of Pb(II) with penicillin benzyl salt (PnB) in 1M KCl containing 40 and 60 % DMF have been made by direct current polarographic technique. Values of stability constants were calculated according to DeFord and Hume's method and it was observed that the reduction on DME was reversible and diffusion controlled involving two electrons. DeFord and Hume's treatment suggest that PnG forms 1:1, 1:2 and 1:3 complexes in all the system mentioned above at 30 and 40 °C. The values of overall stability constants (log β) obtained are 5.27, 7.82 and 11.39 in 40 % DMF, 5.54, 7.97 and 11.51 in 60 % DMF at 30 °C and 5.23, 7.88 and 11.33 in 40 % DMF and 5.43, 7.91 and 11.48 in 60 % DMF at 40 °C.